The Prophet's Tale: Disseminating Religious Narratives and Values in Indonesian Children's Storybooks - Garadian, Endi Aulia; Umam, Saiful (SEMIOTIKA: Jurnal Komunikasi, 2024)
This study investigates the portrayal of Islamic prophets in children’s storybooks published in Indonesia. It utilizes mixed analytical method by combining traditional semiotic analysis and generative artificial intelligence. Focusing on a sample of popular publications, we examine how these narratives visually and textually construct religious stories, aiming to understand their role in shaping children's perceptions of Islamic teachings. The paper reveals the intricate balance between religious fidelity and pedagogical considerations, highlighting a unique cultural synthesis in Indonesian publishing. Our findings demonstrate that while these storybooks adhere closely to Islamic tenets, they also adapt narratives to suit the pedagogical needs of young readers, employing strategies that blend religious teachings with engaging storytelling. The use of generative AI, in this case ChatGPT-4, in conjunction with human analysis offers a comprehensive perspective, identifying patterns that might otherwise be overlooked in traditional methods. This study not only contributes to the field of cultural studies and the understanding of religious narratives in children's literature but also showcases the potential of AI-assisted humanities research. The implications of this research extend to broader discussions on the role of religious narratives in shaping cultural and religious identities in early childhood, offering valuable insights for educators, publishers, and scholars in the field.